PENGARUH STATUS SOSIAL EKONOMI DAN PENDIDIKAN PENGELOLAAN KEUANGAN DI KELUARGA TERHADAP LITERASI KEUANGAN SISWA SMK NEGERI 1 SURABAYA - Romadoni, Romadoni (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
This study aimed to determine the influence of socioeconomic status and financial management education in the family to the financial literacy in 1st State Vocational School of Surabaya academic year 20132014. Population of this study were 197 students. Sampled by 132 students selected by using simple random sampling. Data were collected by questionnaires and documentation. The method of analysis in this study was regression linear. The results showed that the socioeconomic status of parents directly influence financial literacy, financial management education in the family influence on financial literacy and socioeconomic status also family financial education has significant direct effect on financial literacy